Assessment of alternative sources of seaweed polysaccharides in Argentina: potentials of the agarophyte Gelidium crinale (Hare ex Turner) Gaillon (Rhodophyta, Gelidiales) - Croce, Maria Emilia (2015)
The phycocolloids industry in Argentina has been based on the importation of non-native species and the exploitation of natural populations of Gracilaria, which are currently declining. This study was carried out to evaluate the potential of Gelidium crinale as an unexploited source of agar in this country. The yield and composition of polysaccharides extracted from G. crinale, as well as the growth potential of this species were studied. In vitro cultures of apical sections were carried out; relative growth rates (RGR) and data were analyzed through repeated measurements. Explants rapidly duplicated their initial size, producing numerous proliferations and achieving structural complexity. RGR of explants, primary proliferations, and secondary proliferations were high and similar. Polysaccharide extraction was done under three conditions: acid pre-extraction treatment + pressure boiled (AP), water pre-extraction treatment + pressure boiled (WP), and water pre-extraction treatment + boiled (WB). Polysaccharides were characterized through infrared spectroscopy, X-ray fluorescence, thermogravimetric, and elemental analysis. Polysaccharides obtained corresponded to the agar-type, and showed high similarity to commercial agar samples, with low sulfate and methyl contents. Higher yields were obtained with pressure extractions; however, acid treatment did not increase the amount of extracted biopolymers. Their degradation occurred in the range 250–400 °C. Polysaccharides obtained under AP conditions had a degradation curve similar to food-grade agar-agar, whereas degradation curves of polysaccharides obtained without acid treatment were similar to biotechnology-grade agar-agar. According to the results, G. crinale from Anegada Bay produces a high-quality agar to be considered for the Argentinean agar industry; however, micropropagation techniques would be indispensable to increase its bioavailability.